The Power of Basic Math: Preparing Students for a World Beyond the Classroom - Herrle, Reuben; Edwards, Jennifer Flory; Edwards, Michael Todd (Ohio Journal of School Mathematics, 2023)
In this short op-ed, the authors make the argument for the use of real-world contexts to promote student interest and engagement at all levels of instruction.